Heutagogy Approach in Mobile Learning: Developing Technology-Enabled Lifelong Learning - Wiki Lofandri (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Students in higher education are using mobile devices, which challenges our understanding of what it means to learn in modern environments. By using mobile devices as instructional aids, students gain a variety of social, cognitive, and technical abilities. Mobile devices may therefore be seen as supporting the growth of employability skills and broader lifelong learning, both of which may be helpful in a variety of circumstances. The quickly evolving landscape of technology and education presented teachers with a number of challenges, and they had to retrain and refresh their skills in order to provide practical training. As a result, heutagogical methods are ideal for enhancing their collective knowledge and skills. Online and blended learning (BL) offer a learning environment that incorporates technological affordances to facilitate learning. This enables the growth of an independent, capable, and self-directed lifelong learner. Heutagogy provides an educational strategy in this context that may link the development of lifelong learning competencies with BL and online learning environments. Using this methodology, we investigate the potential contribution of online and blended higher education to technology-enabled lifelong learning where heutagogical experiences are available. The results support the notion that heutagogy and lifelong learning are linked by some basic concepts that apply to both mixed and online learning environments.